Investigating the Influence of Mother Tongue Arabic on Using English Prepositions (in, on, at…etc) in Written Production: A Case Study of Second-Year EFL Students at Mohammed Cherief Messaadia University of Souk Ahras, Algeria - Marwa YAHIA (My University, 2025)
Abstract This study aims to investigate the influence of Mother Tongue on the use of English prepositions in written production among second-year EFL students at Mohammed Cherif Messaadia University of Souk Ahras. It specifically seeks to investigate the extent to which Arabic interferes with students' use of English prepositions, resulting in prevalent writing errors that obstruct clarity and precision. A descriptive-analytical technique was employed to attain these objectives. A sample of sixty (60) students was randomly selected, and data were collected through a written test and a structured questionnaire. The research seeks to identify the most common prepositional errors, analyse the differences between Arabic and English prepositional systems, and determine the particular areas where students have the most difficulties. The findings revealed that students frequently misused prepositions such as “in,” “on,” “at,” “to,” and “from”, especially in contexts related to time, place, and direction. These errors were mainly due to negative transfer from Arabic and a tendency to rely on literal translation. A significant number of students also reported choosing prepositions based on what “sounded right,” which often led to incorrect usage. The results demonstrate strong evidence of negative language transfer from Arabic, indicating the necessity for more focused instructional strategies. In response to these results, several pedagogical recommendations and research suggestions are presented to improve preposition acquisition and facilitate further investigations in this linguistic field. ----------------- الملخص تهدف هذه الدراسة إلى التحقيق في تأثير اللغة الأم على استخدام حروف الجر الإنجليزية في الإنتاج الكتابي لدى طلاب السنة الثانية شعبة اللغة الإنجليزية بوصفها لغة أجنبية بجامعة محمد الشريف مساعدية بسوق أهراس. وتسعى بشكل خاص إلى معرفة مدى تدخل اللغة العربية في استخدام المتعلمين لحروف الجر الإنجليزية، مما يؤدي إلى أخطاء شائعة في الكتابة تعيق الوضوح والدقة. تم اعتماد منهج وصفي تحليلي لتحقيق هذه الأهداف، كما تم اختيار عينة عشوائية مكونة من 60 طالبًا، وتم جمع البيانات من خلال اختبار كتابي واستبيان منظم. تسعى الدراسة إلى تحديد أكثر الأخطاء شيوعًا في استخدام حروف الجر، وتحليل الفروق بين نظامي حروف الجر في العربية والإنجليزية، وتحديد المجالات التي يواجه فيها المتعلمون أكبر صعوبات. كشفت النتائج أن الطلاب يسيئون استخدام حروف الجر مثل “in”، “on”، “at”، “to”، و“from” بشكل متكرر، خاصة في السياقات المتعلقة بالزمن والمكان والاتجاه. وترجع هذه الأخطاء في الغالب إلى النقل السلبي من اللغة العربية وإلى ميل الطلاب للاعتماد على الترجمة الحرفية. كما أشار عدد كبير من الطلاب إلى أنهم يختارون حروف الجر بناءً على ما "يبدو صحيحًا" لهم، مما يؤدي غالبًا إلى استخدامات غير دقيقة. تظهر النتائج أدلة قوية على وجود تأثير سلبي للنقل اللغوي من العربية، مما يشير إلى الحاجة إلى استراتيجيات تعليمية أكثر تركيزًا. استجابةً لهذه النتائج، تم تقديم عدة توصيات بيداغوجية واقتراحات بحثية لتحسين اكتساب حروف الجر وتسهيل المزيد من الدراسات في هذا المجال اللغوي. ---------------- Resumé Cette étude vise à examiner l’influence de la langue maternelle sur l’usage des prépositions anglaises dans la production écrite chez les étudiants de deuxième année anglais langue étrangère à l’Université Mohamed Cherif Messaadia de Souk Ahras. Elle cherche plus précisément à déterminer dans quelle mesure l’arabe interfère avec l’utilisation des prépositions anglaises par les apprenants, entraînant ainsi des erreurs fréquentes dans l’écriture qui nuisent à la clarté et à la précision. Une méthode descriptive et analytique a été adoptée pour atteindre ces objectifs. Un échantillon aléatoire de 60 étudiants a été sélectionné, et les données ont été recueillies au moyen d’un test écrit et d’un questionnaire structuré. L’étude cherche à identifier les erreurs prépositionnelles les plus courantes, à analyser les différences entre les systèmes prépositionnels de l’arabe et de l’anglais, et à déterminer les domaines où les apprenants rencontrent le plus de difficultés. Les résultats ont révélé que les étudiants utilisaient fréquemment de manière incorrecte des prépositions telles que “in”, “on”, “at”, “to” et “from”, en particulier dans des contextes liés au temps, au lieu et au mouvement. Ces erreurs étaient principalement dues au transfert négatif de l’arabe et à une tendance à se fier à la traduction littérale. Un nombre important d'étudiants ont également déclaré choisir les prépositions en se basant sur ce qui leur « semblait juste » , ce qui entraînait souvent une utilisation incorrecte. Les résultats montrent des preuves significatives de transfert linguistique négatif de l’arabe, soulignant la nécessité de stratégies pédagogiques plus ciblées. En réponse à ces résultats, plusieurs recommandations pédagogiques et pistes de recherche sont proposées afin d’améliorer l’acquisition des prépositions et d’encourager des recherches ultérieures dans ce domaine linguistique.
Keywords: EFL learners; English prepositions; language transfer; Mother Tongue interference; written production.; متعلمو الإنجليزية بوصفها لغة أجنبية، حروف الجر الإنجليزية، النقل اللغوي، تدخل اللغة الأم، الإنتاج الكتابي.; apprenants d’anglais apprenants d’anglais; prépositions anglaises; transfert linguistique; Interférence de la langue maternelle; production écrite